Metal-organic frameworks-derived CoO/C penetrated with self-supporting graphene enabling accelerated polysulfide conversion for lithium-sulfur batteries. (1st December 2021) - Qu, Meixiu; Bai, Yu; Luo, Min; Sun, Rui; Wang, Zhenhua; Sun, Wang; Sun, Kening
Highlights: The CoO/C nano dodecahedron derived from ZIF-67 possesses high porosity and ample chemical sites for the effective absorption and electrochemical conversion of lithium polysulfides. The unique intercalated microstructure of graphene sheets penetrating through CoO/C polyhedrons provides continuous and rapid charge transfer between conductive matrix and CoO/C, expediting the redox conversion of lithium polysulfides. The self-supported N-rGO@CoO/C as sulfur host for Li-S battery can achieve high areal capacity of 10.0 mA h cm −2 at a relatively high sulfur loading of 9.6 mg cm −2 . Abstract: The lithium-sulfur (Li-S) battery is recognized as one of the most advanced batteries with superior theoretical energy density. Nevertheless, the industrial production of lithium sulfur battery is hindered by the insulation of sulfur and the shuttle behavior of soluble polysulfides. Herein, a freestanding Li-S battery cathode with a unique intercalated microstructure by penetrating graphene sheets into CoO/C polyhedrons is developed as an effective polysulfides reservoir (N-rGO@CoO/C). The unique intercalated microstructure offers continuous and rapid charge transport between the conductive matrix of N-rGO and CoO/C, effectively expediting the redox conversion of lithium polysulfides. Meanwhile, the 3D porous network provides accommodation for storing sulfur and adapts to large volume change. As a result, an impressive initial capacity of 1216 mA h g −1 of the cell with N-rGO@CoO/C can be achieved when sulfur proportion and loading reach 72 wt% and 3.5 mg cm −2, respectively. Moreover, the derived Li-S battery possesses an outstanding areal capacity (10.0 mA h cm −2 ) and excellent cycling stability (capacity retention of 7.47 mA h cm −2 after 150 cycling) even with a very high sulfur loading (up to 9.6 mg cm −2 ). This study offers a feasible way for the development of self-supporting cathode and high-performance Li-S batteries. Abstract : Image, graphical abstract